Designing Instructional Materials for Strengthening Pancasila Student Profile Through Project-Based Learning in Senior High Schools - Toyyibah Toyyibah; Ary Setya Budhi Ningrum; Dewi Nur Suci; Bahruddin Bahruddin; Marwa Mansour (Universitas Pendidikan Mandalika, 2026)
In Indonesia, PjBL is a key component of the Merdeka Curriculum, intended to integrate interdisciplinary learning outcomes with Pancasila values. However, many teachers—even experienced ones—still lack adequate preparation to design and manage PjBL. Integrating several subjects into one project and preparing suitable materials, methods, media, and assessment tools remain challenging tasks. This Research and Development study produced instructional materials for the Project of Strengthening the Pancasila Student Profile (PSPSP) for SMA students. Using the ADDIE framework, this study was conducted only up to the Design and Development stages. The resulting materials cover four project themes: Cultural Exchange and Diversity, Community Service Learning, Environmental Awareness Campaign, and Business Plan/Entrepreneurship. Each project includes detailed implementation steps, handouts and resources, and assessment rubrics with clear criteria and tools. All components were created based on a needs analysis of both teachers and students. The products developed in this study are expected to support SMA English teachers in preparing for PSPSP implementation. Future research that applies and evaluates these materials in real classroom contexts is recommended.